Bentuk Komunikasi Politik untuk Membangun Perilaku Politik Masyarakat Lokal Guna Menciptakan Pemilukada yang Aman - Setyarahajoe, Ratna (Universitas Muhammadiyah Sidoarjo, 2013)
The practice of election should be an important momentum for local people to directly elect the head of terrain. This election studies conducted by the National Law Reform Consortium concluded, that the celebration of democracy in 2010